A qualitative evidence synthesis (QES) exploring the barriers and facilitators to screening in emergency departments using the theoretical domains framework - Louise Barry; Sylvia Murphy Tighe; Anne Griffin; Damien Ryan; Margaret O'Connor; Christine Fitzgerald; Siobhan Egan; Rose Galvin; Pauline Meskell (BMC, 2023)
Abstract Background Validated screening tools can be utilised to detect early disease processes and risk factors for disease and adverse outcomes. Consequently, identifying individuals in need of early intervention and targeted assessment can be achieved through the implementation of screening in the ED. Successful implementation can be impacted by a lack of resources and ineffective integration of screening into the clinical workflow. Tailored implementation processes and staff training, which are contextually specific to the ED setting, are facilitators to effective implementation. This review will assist in the identification of barriers and facilitators to screening in the ED using a QES to underpin implementation processes. Healthcare workers engage in screening in the ED routinely. Consequently, this review focused on synthesizing the experience of healthcare workers (HCWs) who are involved in this process. This synthesis is informed by a QES protocol published by the lead author in 2021 (Barry et al., HRB Open Res 3:50, 2021). Methodology A comprehensive literature search, inclusive of grey literature sources, was undertaken. Initially, an a priori framework of themes was formed to facilitate the interpretation and organisation of search results. A context specific conceptual model was then formulated using "Best fit" framework synthesis which further assisted in the interpretation of data that was extracted from relevant studies. Dual blind screening of search results was undertaken using RAYYAN as a platform. Thirty studies were identified that met the inclusion criteria. Dual appraisal of full text articles was undertaken using CASP, GRADE CERQual assessed confidence of findings and data extraction was performed by two reviewers collaboratively. Findings This is the first known synthesis of qualitative research on HCW's experiences of screening in the ED. Predominantly, the findings illustrate that staff experience screening in the ED as a complex challenging process. The barriers and facilitators identified can be broadly categorised under preconditions to screen, motivations to screen and knowledge and skills to screen. Competing interests in the ED, environmental stressors such as overcrowding and an organisational culture that resists screening were clear barriers. Adequate resources and tailored education to underpin the screening process were clear facilitators. Trial registration PROSPERO: CRD42020188712 05/07/20.